Thrice as easy to catch! Copper and temperature modulate predator‐prey interactions in larval dragonflies and anurans - Mairin T. Hayden; Mari K. Reeves; Marcel Holyoak; Margaret Perdue; Amanda L. King; S. Carl Tobin (Ecosphere, 2015)
Amphibians are important indicators of environmental health, and their populations are in worldwide decline. The causes of these declines are diverse and not well understood. In some cases multiple stressors and complex causal mechanisms have been identified. Experimental studies have shown that contaminants can cause the failure of Lithobates sylvaticus tadpoles to initiate predator avoidance behaviors, potentially leading to increased tadpole capture and injury. Copper is a contaminant known to negatively affect amphibians and other aquatic organisms at sub‐lethal levels. Mining waste, certain pesticides, vehicle exhaust and brake pad dust are sources of copper, which can enter hydrologic systems through runoff. Additionally, temperature is known to influence predator‐prey interactions of ectotherms and is predicted to rise in some areas as climate changes. We examined how copper and temperature affected behavior and predation dynamics between an odonate predator (Aeshna sitchensis) and larval L. sylvaticus prey. We found that sublethal concentrations of copper near the analytical detection limits for this element (1.85 μg Cu/L) significantly reduced tadpole and odonate activity. Above‐average temperatures (22°C) significantly increased tadpole activity and decreased dragonfly activity, compared with ambient‐temperature treatments (17°C). These behavioral responses culminated in an approximately three‐fold increase in the number of dragonfly attacks on tadpoles in the elevated‐temperature, copper‐exposed treatments. We suggest that increased concentrations of dissolved copper and elevated water temperatures are harmful to amphibian prey through maladaptive behavioral responses in the presence of predators.